2016
DOI: 10.1177/0954409716640310
|View full text |Cite
|
Sign up to set email alerts
|

Noise-source identification of a high-speed train by noise source level analysis

Abstract: In this study, noise-source identification of a high-speed train was conducted using a microphone array system. The actual sound pressure level analysis of the noise source was performed using scaling factors between the real sound pressure and the beam-power output based on the assumption that the integrated area of the main beam-power lobe is equal to half that of the actual sound pressure of the noise source. Then, the scaling factors for the 144-channel microphone array were derived from analysis of the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…When studying the far-field noise caused by train operation [4], the rail is usually simplified as a line sound source [5], and the noise radiated in the far field is considered to be consistent with the superposition effect of various individual noise sources in the far field [6]. However, when describing the near-field noise, due to the diversity of the noise sources [7], the propagation characteristics are usually more complex and difficult to be predicted through a simple sound source model. When a train is running at a high speed, the noise sources [8] in the near-field area of the wheel-rail system mainly include the wheelrail rolling noise and aerodynamic noise.…”
Section: Introductionmentioning
confidence: 99%
“…When studying the far-field noise caused by train operation [4], the rail is usually simplified as a line sound source [5], and the noise radiated in the far field is considered to be consistent with the superposition effect of various individual noise sources in the far field [6]. However, when describing the near-field noise, due to the diversity of the noise sources [7], the propagation characteristics are usually more complex and difficult to be predicted through a simple sound source model. When a train is running at a high speed, the noise sources [8] in the near-field area of the wheel-rail system mainly include the wheelrail rolling noise and aerodynamic noise.…”
Section: Introductionmentioning
confidence: 99%
“…7 In addition, because the analysis of the microphone array system is performed based on the beam power value, the array is limited in its ability to analyze the influence of the actual sound pressure of the pantograph. 8 In order to investigate the effect of noise from the pantographs of high-speed railway vehicles, studies using wind tunnel tests were widely used. 9,10 In those studies, noise sources and characteristics generated from a small-scale pantograph model were identified through sound field visualization using a microphone array.…”
Section: Introductionmentioning
confidence: 99%
“…He et al [8] investigated the external noise of a highspeed train at different speeds and found that the rolling noise has a greater contribution to the total noise than the aerodynamic noise. Noh [9] used a microphone array to identify the noise sources of a high-speed train and found that the main noise sources are the intercoach spacing, wheels, and pantograph, when the train is running at 390 km/h. e different conclusions are related to the different vehicle types, track types, and train speeds in their studies.…”
Section: Introductionmentioning
confidence: 99%